Free Convection Boundary Layer Flow of a Horizontal Circular Cylinder in a Micropolar Fluid with Convective Boundary Conditions - Norhafizah, Md Sarif; Mohd Zuki, Salleh; Razman, Mat Tahar; Roslinda, Nazar (2013)
The free convection boundary layer flow over a horizontal circular cylinder has received much attention in recent years due to its application in physical, geophysical, and industrial fields. It appears that [Merkin, 1976] was the first to has presented a complete solution of this problem for a classical(Newtonian) fluid, using Blasius and Gortler series expansion method along with an integral method and finite difference scheme. Following Merkin’s work, [Nazar et al., 2002] studied the similar problem but immersed in a microplar (non-Newtonian) fluid by applying constant wall temperature in the boundary. Therefore, the aim of the present paper is to investigate the free convection boundary layer flow of a horizontal circular cylinder in a micropolar fluid with convective boundary conditions. The transformed boundary layer equations in the form of ordinary differential equations are solved numerically using an implicit finite-difference scheme, namely Keller-box method. Numerical results are obtained for the skin friction coefficient and wall temperature as well as in velocity and temperature profiles.